2022
DOI: 10.3390/ijms232012656
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Pulmonary Hypertension and Edema Induced by Hypobaric Hypoxia Exposure

Abstract: Exposure to high altitudes generates a decrease in the partial pressure of oxygen, triggering a hypobaric hypoxic condition. This condition produces pathophysiologic alterations in an organism. In the lung, one of the principal responses to hypoxia is the development of hypoxic pulmonary vasoconstriction (HPV), which improves gas exchange. However, when HPV is exacerbated, it induces high-altitude pulmonary hypertension (HAPH). Another important illness in hypobaric hypoxia is high-altitude pulmonary edema (HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In our study, we found that the simulated hypobaric hypoxic environment resulted in increased secretion of pro-inflammatory cytokines, such as IL-6 and TNF-α, in rat serum, and inflammatory cell infiltration was also observed in heart tissue, while pre-administration of NG-R1 attenuated the cardiac inflammatory response caused by hypobaric hypoxia, as evidenced by pathologically reduced inflammatory cell infiltration at the site of cardiac injury in specimens and the corresponding reduction in serum levels of IL-6 and TNF-α in rats. Previous studies have confirmed that elevated pro-inflammatory cytokines, such as TNF and IL-6, can induce apoptosis in cardiac myocytes by either directly having a pathway to apoptosis or indirectly by stimulating NO or ROS production (Courties et al, 2014;Ellison-Hughes et al, 2020). However, NG-R1 has shown obvious anti-inflammatory and anti-apoptosis properties in previous studies.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In our study, we found that the simulated hypobaric hypoxic environment resulted in increased secretion of pro-inflammatory cytokines, such as IL-6 and TNF-α, in rat serum, and inflammatory cell infiltration was also observed in heart tissue, while pre-administration of NG-R1 attenuated the cardiac inflammatory response caused by hypobaric hypoxia, as evidenced by pathologically reduced inflammatory cell infiltration at the site of cardiac injury in specimens and the corresponding reduction in serum levels of IL-6 and TNF-α in rats. Previous studies have confirmed that elevated pro-inflammatory cytokines, such as TNF and IL-6, can induce apoptosis in cardiac myocytes by either directly having a pathway to apoptosis or indirectly by stimulating NO or ROS production (Courties et al, 2014;Ellison-Hughes et al, 2020). However, NG-R1 has shown obvious anti-inflammatory and anti-apoptosis properties in previous studies.…”
Section: Discussionmentioning
confidence: 89%
“…However, excessive and abnormal changes can cause or even exacerbate acute mountain sickness (AMS), which is one of the most common high‐altitude diseases (Guo et al, 2017; Zila‐Velasque et al, 2023). The inability to adapt to high‐altitude‐induced hypoxia could rapidly result in high‐altitude cardiac injury (HACI) (Pan et al, 2022), high‐altitude pulmonary edema (HAPE) (El Alam et al, 2022), and high‐altitude cerebral edema (HACE) (Xue et al, 2022). High altitude‐induced hypoxia, sympathetic activation, and alkalosis can be the predisposing factors for cardiac ischemia and arrhythmia (Woods et al, 2011), with excessive oxidative stress and inflammatory response leading to apoptosis of cardiomyocytes (Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…(40) However, a previous study showed that CRP of healthy subjects and patients with pulmonary oedema was increased after acute exposure to HA, most likely due to acute hypoxia stimulate in ammation by the way of nuclear factor kappa B (NF-κB) gene transcription and the production of proin ammatory cytokines. (41)(42)(43) The reasons for the difference might be that our subjects were permanent residents of their altitude, and the subjects of other studies with inverse result were acute exposure to HA, moreover, our study had larger sample sizes, different disease condition and different race.…”
Section: Multivariate Logistic Regression Analysis Indicated That The...mentioning
confidence: 89%
“…While in high-altitude pulmonary hypertension (HAPH), inflammatory pathways may importantly contribute to the proliferation of pulmonary artery smooth muscle cells and pulmonary hypertension [ 75 ], this may not be the case for HAPE. Although inflammation in HAPE could contribute to increased alveolar-capillary permeability, studies in humans rather indicate that inflammation constitutes a secondary response to the pulmonary edema and/or disruption of the alveolar-capillary barrier, not a primary factor in HAPE pathogenesis [ 72 ].…”
Section: High Altitude Illnesses: Epidemiology and Pathophysiologymentioning
confidence: 99%